Psychometric properties of the Ryerson Social Anxiety Scales in individuals with social anxiety disorder. Issue 5 (3rd September 2021) - Tsekova, Virginia; Lenton-Brym, Ariella P.; Rogojanski, Jenny; Hood, Heather K.; Vorstenbosch, Valerie; McCabe, Randi E.; Antony, Martin M.
ABSTRACT: Background: Although numerous self-report measures of social anxiety exist, most instruments assess symptom severity by examining the range of social situations that provoke anxiety, rather than the distress and impairment associated with social anxiety. The Ryerson Social Anxiety Scales (RSAS; Lenton-Brym, A. P., Rogojanski, J., Hood, H. K., Vorstenbosch, V., McCabe, R. E., & Antony, M. M. (2020). Development and validation of the Ryerson Social Anxiety Scales (RSAS). Anxiety, Stress, & Coping, 33(6), 642–660), a measure assessing breadth of social anxiety inducing situations and severity of associated distress and impairment, was recently developed to fill this gap. The present study is the first to investigate the psychometric properties of the RSAS in a clinical sample. Method/Design: Participants included 110 individuals with a principal diagnosis of social anxiety disorder (SAD). A subsample of participants ( n = 23) completed cognitive–behavioural group treatment (CBGT) for SAD. Results: The RSAS demonstrated excellent internal consistency. Examination of the correlations between the RSAS and other conceptually related and distinct measures supported the convergent and discriminant validity of the RSAS. The RSAS was also sensitive to changes in severity of social anxiety following CBGT. Conclusion: The RSAS is a reliable and valid instrument for assessing the severity of SAD.